The impact of local regulation on reasons for electronic cigarette use among Southern California young adults. (April 2019) - Hong, Hanna; McConnell, Rob; Liu, Fei; Urman, Robert; Barrington-Trimis, Jessica L.
Abstract: Objective: Tobacco control policies have decreased tobacco use among youth and young adults. We aimed to identify whether specific local tobacco retail licensing ordinances were associated with reasons for e-cigarette use, in order to examine whether strong local policies may reduce e-cigarette initiation rates by influencing the appeal of these products. Methods: Online questionnaires were completed by Southern California Children's Health Study participants in 2015–2016 (mean age = 18.9 years). Those who had ever used an e-cigarette ( N = 614) were asked about reasons for use; additional data were collected on local jurisdiction tobacco sales policy, friends' attitudes toward e-cigarette use, e-cigarette characteristics (level of nicotine, flavorings), and history of tobacco use. Multivariate logistic regression models evaluated associations of each factor with reasons for e-cigarette use, adjusting for gender, ethnicity, highest parental education, tobacco use history and with a random effect of jurisdiction. Results: The top reason for e-cigarette use was "They come in flavors I like" (56.6%). Using e-cigarettes to quit smoking was uncommon (12.8%). Participants in jurisdictions with weaker tobacco retail licensing ordinances were more likely to report use of e-cigarettes because they are less harmful than cigarettes (50.1% vs. 36.2%), more acceptable to non-tobacco users (38% vs. 25%), and because they can use e-cigarettes in places where smoking is prohibited (30.7% vs. 18.3%; all p < .05). Conclusion: Targeted policy to enforce a strong regulatory environment that denormalizes e-cigarette use, conveys the adverse impact of e-cigarettes, and restricts use in public places may reduce e-cigarette use among adolescents and young adults. Highlights: The impact of local tobacco licensing policies on reasons for e-cigarette use has not been studied. Reasons for e-cigarette use differed by the strength of local policy enforcement. In weakly enforced localities, less harm, acceptability, use in cigarette-prohibited areas were cited more frequently. Reasons for e-cigarette use may be important in developing effective interventions and policies to reduce use.